Imerys extends capacity for conductive carbon black at Belgian plant. Issue 2 (February 2015) - Unknown
Abstract : Imerys Graphite & Carbon reports that it has successfully commissioned a second production line for conductive carbon blacks at its Willebroek facility in Belgium. The expansion effectively doubles the plant's production capacity. Imerys has reportedly invested some €20 million in the expansion project, which also included updating key plant infrastructure such as the steam management system.